Evaluación del bachillerato en contabilidad informatizada, modalidad a distancia del colegio Pío Jaramillo Alvarado de la ciudad de Loja. Periodo 2010-2011. Lineamientos propositivos - Ocampo Ordoñez, Raquel Aurelina (2014)
The present research work entitled BACHILLERATO ASSESSMENT OF COMPUTERIZED ACCOUNTING, DISTANCE EDUCATION SYSTEM OF PÍO JARAMILLO ALVARADO HIGH SCHOOL OF LOJA CITY ACADEMIC PERIOD 2010-2011, has been established with the purpose of evaluating the quality of the Bachillerato in Computerized Accounting. It was based on a non-experimental design, which allowed the researcher to question reality, describe information, verify goals and establish the respective conclusions and recommendations. The main methods applied to develop this research work were scientific, inductive, deductive, descriptive, bibliographic, analytic-synthetic and statistical. The survey was used to obtain information from 4 authorities, 4 teachers and 32 students, giving a total of 40 respondents. The main results of the research show that a curricular evaluation does not exist. It was found that the level of knowledge that the 32 students have, is half and the equipment and technological means are not widely used by teachers or students. Therefore, to meet this last result, a workshop entitled “Workshop on the Use and Application of New Information Technologies and Communication in Teaching and Learning Processes in Distance Education system” has been proposed to improve the quality of education in Computerized Accounting. It was concluded that the virtual platform is outdated and does not allow interaction between teachers and students of the Bachillerato evaluated. For this reason it is necessary to redesigning the curriculum in order to, students and teachers will be able to achieve the educational goals and objectives set by the institution.